Effect of arsenic trioxide on the Tregs ratio and the levels of IFN-γ, IL-4, IL-17 and TGF-β1 in the peripheral blood of severe aplastic anemia patients. Issue 26 (26th June 2020) - Zhao, Juanjuan; Song, Yongping; Liu, Lina; Yang, Shiwei; Fang, Baijun
Abstract : Abstract: Previous studies have suggested that the anticancer agent, arsenic trioxide (ATO), could attenuate T cell mediated immunity by not only inhibiting the proliferative response of T cells but by also increasing the frequency of regulatory T cells (Tregs). Furthermore, ATO represents a reasonable salvage treatment in some patients with refractory severe aplastic anemia (SAA). The current study aimed to evaluate the function of ATO on the Tregs percentage and cytokines changes in the peripheral blood mononuclear cells (PBMCs) of SAA patients. PBMCs were collected from 20 newly diagnosed SAA patients in Henan Cancer Hospital and treated with different concentrations of ATO (0, 1, 2.5, and 5 μmol/L). Then we investigated the efficacy of ATO on Tregs ratio and the levels of interferon (IFN)-γ, interleukin (IL)-4, IL-17 and transforming growth factor (TGF)-β1 in the peripheral blood of SAA patients in vitro. The results showed that ATO significantly increased the proportion of Tregs ( P < .001) at 2.5 and 5 μmol/L concentrations, and the proportion of Tregs was increased with increasing ATO concentration (r = 0.524). At 1 ( P = .03), 2.5 ( P < .001) and 5 μmol/L ( P < .001), ATO significantly up-regulated the expression levels of Foxp3 mRNA, which was positively and linearly correlated with the increase of Tregs cell-frequency ( r = 0.52, 95%CI, 0.37–0.67). In addition, ATO significantly reduced the levels of IFN-γ (at 1, 2.5 and 5 μmol/L, P < .001), IL-4 (at 2.5 μmol/L, P = .009; at 5 μmol/L, P < .001), and IL-17 (at 2.5, P = .016; at 5 μmol/L, P < .001). ATO significantly reduced the levels of TGF-β1 at 5 μmol/L ( P = .03), but showed no significant effects at 1 and 2.5 μmol/L ( P > .05). ATO could mediate the immune regulation, which might contribute to improve hematopoietic recovery in SAA patients.